The dorsal scapular artery in the lower third of the trapezius muscle - João Lorenzo Bidart Sampaio Rocha; Geruza Rezende Paiva; Lorenzo Carvalho Sampaio Rocha (Revista Brasileira de Cirurgia Plástica, 2021)
Introduction: The dorsal scapular artery angiosome (DSAA) has aroused growing interest among repairing surgeons, although the most common applications of the trapezoid muscle (TM) are by the arc of rotation of the transverse cervical artery (TCA) and its angiomoses, more cephalic, sufficient for reconstruction purposes in the head and neck. The possibility of obtaining flaps of large cutaneous territory for reconstructions on the back stimulates the study of DSAA angiomoses. Methods: Eight sides of four fresh cadavers were dissected for DSAA investigation, and 60 sides of 30 volunteers were examined by color Doppler echo in search of DSAA. Results: Two patterns were described in the course of DSAA in dissections, both irrigating the region of the lower third of the TM. Doppler echo-examination detected emergence and course of DSAA for the lower third of The TM bilaterally in 27 of the volunteers, in two only on the left and was not identified anywhere in one of the volunteers. Conclusion: There may be two patterns in the course of DSAA irrigating the region of the lower third of the TM. The color Doppler echo-examination determined the emergence and the Path of the DSAA on 56 of the 60 sides examined.